Concentration Evaluation and Health Risk Assessment of Welders\' Exposure to Total Fumes and Manganese during Welding at Metal Industry - Mahmud Mohammadian; Esmaeil Babanezhad; Jamshid Yazdani charati; Yahya Esfandiari; Solale Ramzani (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Risk assessment of toxic or hazardous chemicals enables industrial hygienists to make appropriate decisions regarding management provisions in a healthy workplace. Exposure to total fumes and manganese during welding can have harmful effects on welders' health. Therefore, the present study was conducted in the metal industry to evaluate the concentration and determine the risk of welders' exposure to total fumes and manganese in 2018. Methods: In this descriptive-analytical and cross-sectional study, welding fumes were sampled in the breathing zone of 35 welders using filters and cyclones moreover, the concentration of fumes was determined by a weight method. The samples were analyzed according to NIOSH 7301 method using an Inductively Coupled Plasma-Optical Emission Spectrometry to determine the manganese concentration in the fume. Moreover, health exposure risk assessment of workers exposed to welding fumes was performed using the recommended method by the Singapore Health and Safety Association method. The data were analyzed in MINITAB software (version 17). A p-value less than 0.05 was considered statistically significant.    Results: The mean concentrations of total fumes and manganese produced in Shielded Metal Arc were 9.56±1.67 and 0.45±0.08 mg/m-3, respectively. These values are about 2 and 22 times higher than the recommended occupational threshold limit for total fumes and manganese according to the American Conference of Governmental Industrial Hygienists, respectively. The risk assessment results showed that the mean values of exposure to total and manganese fume for the welders were moderate and high, respectively. Conclusion: Due to the high level of welders' exposure to manganese during welding in the metal industry, preventive measures, such as engineering and management control techniques are recommended to reduce exposure to these fumes.